Does the SARS-CoV-2 rapid antigen test result correlate with the viral culture result?. Issue 8 (August 2021) - Yamamoto, Kei; Nagashima, Mami; Yoshida, Isao; Sadamasu, Kenji; Kurokawa, Masami; Nagashima, Maki; Kinoshita, Noriko; Maeda, Kenji; Takasaki, Jin; Teruya, Katsuji; Ohmagari, Norio
Abstract: Rapid antigen tests (RATs) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have advantages over viral culture in terms of cost and rapidity of testing, but they have low sensitivity. In addition, RATs tend to be negative from approximately 11 days after symptom onset. To determine whether the antigen-negative state indicates a lack of infectiousness, we assessed the association between viral culture and RAT results. Viral culture, reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and rapid antigen testing were performed on stored nasopharyngeal samples with threshold cycle values < 30, based on previous RT-qPCR testing. SARS-CoV-2 was isolated by viral culture from nine samples (45%) and one sample (17%) with positive and negative RAT results, respectively. The RAT and viral culture results were both associated with the viral load level and their cutoffs were similar, but the associations were not statistically significant. RAT might be a useful indicator of infectiousness, which can be helpful to control infection. However, further studies with larger sample size are warranted to confirm this observation.